A new species and a new country record in the genus Protaetia Burmeister, 1842 (Coleoptera: Scarabaeidae: Cetoniinae) from Vietnam - Mückstein, Petr (Zootaxa, 2021)
Protaetia (Macroliocola) dianae Mückstein, a new species of fruit chafer (Coleoptera: Scarabaeidae: Cetoniinae) from northern Vietnam is described. Habitus and diagnostic features of the new species are illustrated. A new country record of Protaetia (Liocola) miharai (Alexis & Delpont, 1998) for Vietnam is presented.